SISTEM EVALUASI RAHMAH DALAM PENDIDIKAN: PENDEKATAN HUMANIS UNTUK MENILAI PROSES DAN HASIL BELAJAR PESERTA DIDIK - Sri Etika; Dona Fitria; Emisda; Taufiq Ismail; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning evaluation is a crucial component of the educational system that functions to measure the achievement of learning objectives. However, evaluation practices that focus solely on learning outcomes often neglect aspects of humanity, fairness, and the individual conditions of students. This article aims to examine the concept and implementation of the rahmah-based evaluation system in education as a humanistic, fair, and empathy-oriented evaluation approach. The rahmah evaluation system emphasizes the learning process, holistic student development, and the provision of constructive feedback without causing psychological pressure. The method employed in this study is a literature review by analyzing various sources related to educational evaluation, humanistic approaches, and rahmah values in learning. The findings indicate that the rahmah evaluation system is capable of creating a more positive learning environment, increasing students’ learning motivation, and promoting balanced cognitive, affective, and psychomotor development. Therefore, the rahmah evaluation system can serve as a relevant alternative evaluation approach in the context of modern education that is oriented toward character development and human values.